MODERN ECONOMIC MODELS AND AZERBAIJAN - R. Guliyev (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The article has an excursion into the modern economic theory. The current global economic models of socio -economic development are con-sidered. The differences that exist between these models are analyzed. The main difference between the models of socio-economic development associated with the role of the state in a market economy is pointed out. The characteristic of the Azerbaijani model of socio-economic develop-ment and its basic elements are cited. The importance of the oil strategy of the country, which is an essential element of social-economic develop-ment of Azerbaijan, is emphasized. The analysis of trends in the successful development of the national economy is given. Conclusions about the success of the Azerbaijani model of socio-economic development are made.